FKBPL Is a Critical Antiangiogenic Regulator of Developmental and Pathological Angiogenesis. Issue 4 (April 2015) - Yakkundi, Anita; Bennett, Rachel; Hernández-Negrete, Ivette; Delalande, Jean-Marie; Hanna, Mary; Lyubomska, Oksana; Arthur, Kenneth; Short, Amy; McKeen, Hayley; Nelson, Laura; McCrudden, Cian M.; McNally, Ross; et al.
<x xml:space="preserve">Abstract</x> Objective— The antitumor effects of FK506-binding protein like (FKBPL) and its extracellular role in angiogenesis are well characterized; however, its role in physiological/developmental angiogenesis and the effect of FKBPL ablation has not been evaluated. This is important as effects of some angiogenic proteins are dosage dependent. Here we evaluate the regulation of FKBPL secretion under angiogenic stimuli, as well as the effect of FKBPL ablation in angiogenesis using mouse and zebrafish models. Approach and Results— FKBPL is secreted maximally by human microvascular endothelial cells and fibroblasts, and this was specifically downregulated by proangiogenic hypoxic signals, but not by the angiogenic cytokines, VEGF or IL8. FKBPL's critical role in angiogenesis was supported by our inability to generate an Fkbpl knockout mouse, with embryonic lethality occurring before E8.5. However, whilst Fkbpl heterozygotic embryos showed some vasculature irregularities, the mice developed normally. In murine angiogenesis models, including the ex vivo aortic ring assay, in vivo sponge assay, and tumor growth assay, Fkbpl+/− mice exhibited increased sprouting, enhanced vessel recruitment, and faster tumor growth, respectively, supporting the antiangiogenic function of FKBPL. In zebrafish, knockdown of zFkbpl using morpholinos disrupted the vasculature, and the phenotype was rescued with hFKBPL. Interestingly, this vessel disruption was ineffective when zcd44 was knocked-down, supporting the dependency of zFkbpl on zCd44 in zebrafish. Conclusions— FKBPL is an important regulator of angiogenesis, having an essential role in murine and zebrafish blood vessel development. Mouse models of angiogenesis demonstrated a proangiogenic phenotype in Fkbpl heterozygotes.